Occurrence of plasmid-mediated quinolone resistance genes in Escherichia coli and Klebsiella spp. recovered from Corvus brachyrhynchos and Corvus corax roosting in Canada - Janecko, N; Halova, D; Jamborova, I; Papousek, I; Masarikova, M; Dolejska, M; Literak, I (Letters in applied microbiology, 2018)
UNLABELLED: The spread of antimicrobial resistance from human activity derived sources to natural habitats implicates wildlife as potential vectors of antimicrobial resistance transfer. Wild birds, including corvid species can disseminate mobile genetic resistance determinants through faeces. This study aimed to determine the occurrence of plasmid-mediated quinolone resistance (PMQR) genes in Escherichia coli and Klebsiella spp. isolates obtained from winter roosting sites of American crows (Corvus brachyrhynchos) and common ravens (Corvus corax) in Canada. Faecal swabs were collected at five roosting sites across Canada. Selective media isolation and multiplex PCR screening was utilized to identify PMQR genes followed by gene sequencing, pulse-field gel electrophoresis and multilocus sequence typing to characterize isolates. Despite the low prevalence of E. coli containing PMQR (1·3%, 6/449), qnrS1, qnrB19, qnrC, oqxAB and aac(6')-Ib-cr genes were found in five sequence types (ST), including E. coli ST 131. Conversely, one isolate of Klebsiella pneumoniae contained the plasmid-mediated resistance gene qnrB19. Five different K. pneumoniae STs were identified, including two novel types. The occurrence of PMQR genes and STs of public health significance in E. coli and Klebsiella pneumoniae recovered from corvids gives further evidence of the anthropogenic derived dissemination of antimicrobial resistance determinants at the human activity-wildlife-environment interface. SIGNIFICANCE AND IMPACT OF THE STUDY: This study examined large corvids as possible vector species for the dissemination of antimicrobial resistance in indicator and pathogenic bacteria as a means to assess the anthropogenic dissemination of plasmid-mediated quinolone resistance (PMQR) genes. Although rare, PMQR genes were found among corvid populations across Canada. The clinically important Escherichia coli strain ST131 containing aac(6')-Ib-cr gene along with a four-class phenotypic antimicrobial resistance (AMR) pattern as well as one Klebsiella pneumoniae strain containing a qnrB19 gene were identified in one geographical location. Corvids are a viable vector for the circulation of PMQR genes and clinically important clones in wide-ranging environments.
Keywords: Animals; antimicrobial resistance; chinolony; Escherichia coli Infections; Quinolones; infekce vyvolané Escherichia coli; PMQR genes; mikrobiální testy citlivosti; Escherichia coli; Kanada; průřezové studie; ST131; Klebsiella Infections; E. coli; lidé; nemoci ptáků; Anti-Bacterial Agents; multilokusová sekvenční typizace; bakteriální léková rezistence; infekce bakteriemi rodu Klebsiella; Crows; Bird Diseases; Microbial Sensitivity Tests; Canada; Cross-Sectional Studies; plazmidy; vrány; Multilocus Sequence Typing; Plasmids; zvířata; antibakteriální látky; Drug Resistance, Bacterial; Klebsiella pneumoniae; Humans